Effects of growth regulators on root tip cells of onion - Ud-Deen, Md Mosleh; Kabir, Golam (Bangladesh Journal of Botany, 2010)
Cell size and mitotic index were decreased with increasing concentrations of growth regulators such as GA3, uniconazole, chlorocholine chloride (CCC) and 2,3,6-TBA while nuclear volume, interphase chromosome volume and abnormalities were found to increase during division of onion root tip cells. Formation of chromosome fragments, bridges, laggards, single and multiple chromatid bridges, irregular distribution and unequal separation of chromosomes were visualized as the main effects due to the application of these growth regulators. Key words: Growth regulators; Onion; Root tip cell; Chromosome abnormalities DOI: 10.3329/bjb.v38i1.5130 Bangladesh J. Bot. 38(1): 55-63, 2009 (June)